KUALITAS TIDUR MAHASISWA KEPERAWATAN TINGKAT DUA - Desi Maranata Hutasoit; Inez Jane Mendrofa; Maria Maxmila Yoche Arkianti; Catharina Guinda Diannita (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2024)
Background: Poor sleep quality can lead to cognitive impairment, difficulty concentrating, and various other health problems. Nursing students are one of those who have the potential to experience sleep quality problems. Purpose: To obtain an overview of the sleep quality of second-year nursing students at a private university in Western Indonesia. Methods: A descriptive quantitative approach was used in this study. The population of this study was second year nursing students at one of the private universities located in Western Indonesia with a total of 173 students and the sampling method was total sampling. The research instrument to measure sleep quality was the Pittsburgh Sleep Quality Index (PSQI) questionnaire in Indonesian language. For this research data, univariate analysis was carried out using computerization. Results: The respondents were 87.9% female and 12.1% male, and it was found that 85 per cent of the respondents had poor sleep quality and 15 per cent had good sleep quality. Implication: In this study, most of the sophomores were female, and they had poor sleep quality. Students are advised to make a daily plan to improve their sleep quality and follow it regularly to fulfil their sleep needs.